When TikTok Influences Brands: Understanding the Impact of Digital Attitudes on Consumption among Tunisian Gen Z - NAJAR, Manel; MAGHRAOUI, Souad (Revue Internationale du Chercheur, 2025)
This research investigates how the e-lifestyle of young Tunisians shapes their attitudes toward TikTok and how these attitudes translate into brand-related behavioral and attitudinal outcomes. Grounded in a consumer–brand relationship perspective, the study examines the influence of digital lifestyle on users’ attitudes toward the platform, as well as the effects on brand attachment and purchase intention. The moderating role of self–platform congruence, reflecting the perceived alignment between users’ identity and the identity conveyed by the platform and its promoted brands, is also assessed. The empirical study targets Tunisian Generation Z users aged 15 to 29. The data were collected using a non-probabilistic convenience sampling method through an online questionnaire distributed via social media, from a sample of 300 participants. The conceptual model was tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that positive attitudes toward TikTok encourage sustained platform use and strengthen brand attachment. This attachment significantly predicts purchase intention, confirming its key role in digital consumer behavior. Moreover, self–platform congruence amplifies the effect of positive attitudes on purchase intention. The study highlights the importance of integrating e-lifestyle and identity congruence when analyzing brand responses within social media environments.